2005
DOI: 10.1051/lait:2004028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acquired resistance to bile salts on enzymatic activities involved in the utilisation of carbohydrates by bifidobacteria. An overview

Abstract: -Bifidobacteria are probiotics widely used in dairy-based products. In order to exert the health-promoting benefits attributed to these microorganisms, they must survive the restrictive conditions of the gastrointestinal tract, being resistant, among other factors, to the toxic action of bile salts. The inhibition exerted by these compounds on bifidobacteria can be overcome by progressive adaptation to gradually increasing concentrations of bile. The acquisition of stable resistance, or even transient exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Also it is found that the Bifidobacteria degrade bile salts, this criterion probiotic is due to an enzyme that hydrolyzes bile salts (BHS) [15], this enzyme was isolated from the stem Bifidobacterium longum BB536 [16], and in strain Bifidobacterium longum SBT2928 [17]. Adaptive mechanisms of tolerance to bile salts could lead to better adaptation to the environment and colonic available carbon sources and a persistent increase in the viability of Bifidobacterium in the intestinal environment [18,19].…”
Section: Br1 Br2 Bl1 Bl2mentioning
confidence: 99%
“…Also it is found that the Bifidobacteria degrade bile salts, this criterion probiotic is due to an enzyme that hydrolyzes bile salts (BHS) [15], this enzyme was isolated from the stem Bifidobacterium longum BB536 [16], and in strain Bifidobacterium longum SBT2928 [17]. Adaptive mechanisms of tolerance to bile salts could lead to better adaptation to the environment and colonic available carbon sources and a persistent increase in the viability of Bifidobacterium in the intestinal environment [18,19].…”
Section: Br1 Br2 Bl1 Bl2mentioning
confidence: 99%